Activation of H2 by a Multiply Bonded Amido–Digermyne: Evidence for the Formation of a Hydrido–Germylene1. Issue 39 (12th August 2013) - Hadlington, Terrance J.; Hermann, Markus; Li, Jiaye; Frenking, Gernot; Jones, Cameron
<x xml:space="preserve">Abstract</x> The long and the short of it. The first amido–digermyne to possess a short Ge–Ge multiple bond, [LGeGeL], has been prepared and shown to activate H2 below 0 °C, thereby yielding the hydrido–digermene, [L(H)GeGe(H)L]. This possesses a very long GeGe bond. Spectroscopic and theoretical data indicate that the dimer dissociates in solution to give the two‐coordinate hydrido–germylene, [:Ge(H)(L)]. L=N(Ar)(SiiPr3), Ar=2, 6‐[C(H)Ph2]2‐4‐iPrC6H2.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>